Antibacterial study and phytochemical screening on the root extract of Mimusops elengi / Nur Hidayah Che Hamri - Che Hamri, Nur Hidayah (2016)
Petroleum ether, chloroform and methanol extracts of Mimusops elengi roots were investigated for antibacterial activity against the human pathogenic bacteria Escherichia coli and Staphylococcus aureus. Five different concentrations of all three extracts consisting of 25, 50, 100, 200 and 400 µg/µl were prepared for testing antibacterial activity using disc diffusion method. The results revealed that all the three extracts showed antibacterial activity against both bacterial tested. However, petroleum ether and chloroform extracts were found to be more effective and exhibit better inhibiting activity against gram negative bacteria, E. coli compared to gram positive bacteria, S. aureus. Meanwhile methanol extract was found to be more effective and exhibit better inhibiting activity against gram positive bacteria, S. aureus compared to gram negative bacteria, E. coli. Methanol extract of M. elengi root also shows greater inhibition zone compared to petroleum ether and chloroform extract as phytochemical screening revealed that this extracts contain saponins and alkaloids. The highest antibacterial activity was exhibited by 400 µg/µl methanolic extracts against S. aureus which inhibited 14.00 ± 2.36 rom of the diameter zone. This result revealed the potentials of M. elengi as antibacterial agent in combating infections from human pathogenic bacteria. However, further studies, including identification and purification of the active compounds, will need to be pursued.